1995
DOI: 10.1021/jm00024a009
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure-Activity Relationships of Acetylcholinesterase Inhibitors: 1-Benzyl-4-[(5,6-dimethoxy-1-oxoindan-2-yl)methyl]piperidine Hydrochloride and Related Compounds

Abstract: Following the discovery of a new series of anti-acetylcholinesterase (anti-AChE) inhibitors such as 1-benzyl-4-[2-(N-benzoylamino)ethyl]piperidine (1), we reported that its rigid analogue, 1-benzyl-4-(2-isoindolin-2-ylethyl)piperidine (5), had more potent activity. We have extended the structure-activity relationship (SAR) study for the rigid analogue and found that the 2-isoindoline moiety in compound 5 can be replaced with a indanone moiety (8) without a major loss in potency. Among the indanone derivatives,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
180
0
4

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 311 publications
(191 citation statements)
references
References 25 publications
7
180
0
4
Order By: Relevance
“…Donepezil powerfully inhibits acetylcholinesterase (17) and elevates acetylcholine concentration in the synapse, which results in increased cholinergic transmission. Previous studies have suggested the donepezil has neuroprotective effects aside from its acetylcholinesterase-inhibiting action through up-regulation of Bcl-2, an anti-apoptotic protein (18), stimulation of nicotinic acetylcholine receptors (19), and inhibition of glycogen synthase kinase-3 (GSK-3) activity (20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Donepezil powerfully inhibits acetylcholinesterase (17) and elevates acetylcholine concentration in the synapse, which results in increased cholinergic transmission. Previous studies have suggested the donepezil has neuroprotective effects aside from its acetylcholinesterase-inhibiting action through up-regulation of Bcl-2, an anti-apoptotic protein (18), stimulation of nicotinic acetylcholine receptors (19), and inhibition of glycogen synthase kinase-3 (GSK-3) activity (20).…”
Section: Discussionmentioning
confidence: 99%
“…It is unknown whether donepezil exerts its neuroprotective effect in rats subjected to repeated cerebral ischemia. Induction of the neuroprotective effects of donepezil via the nicotinic acetylcholine receptor in rats subjected to repeated cerebral ischemia may require a higher concentration and/or long-term treatment because the concentration of donepezil showing neuroprotection is higher than the concentration needed to exhibit acetylcholinesterase-inhibiting action in vitro (17,19,20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acetylcholinesterase (AChE) hydrolyzes the neurotransmitter acetylcholine (ACh) and is the most widely used target enzyme in studies with the purpose to synthesize new and more effective therapeutic agents to treat patients with diseases such as Alzheimer's disease (AD) or myasthenia gravis [7][8][9] . Reversible inhibition of brain AChE by anti-AD drugs such as tacrine 10 , donepezil 11 , and huperzine 12 increases the ACh levels and improves neurotransmission in cholinergic synapses 13 . AChE is also used widely as a target in the studies of compounds with insecticidal activities, as all commercially available organophosphate compounds are believed to exert their effects through potent reversible or irreversible inhibition of this enzyme 14 .…”
Section: Introductionmentioning
confidence: 99%
“…A rigidez e a planaridade são características importantes deste esqueleto, que está presente em diversas moléculas com atividade biológica de interesse, incluindo fármacos em comercialização, como o Indinavir ® um inibidor da HIV-protease 1,2 e o Aricept ® utilizado no tratamento do mal de Alzheimer 3,4 …”
Section: Introductionunclassified